ASOSIASI HUMAN LEUKOCYTE ANTIGEN (HLA) KARSINOMA NASOFARING (KNF) - F.M. Judajana (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Nasopharyngeal Carcinoma (NPC) is one of the most frequent malignancy disease in Java and the incidence rate at several Hospitalsseems increasing yearly. Prevalence of NCP in Indonesian were 3.9 per 100.000 citizen each year. Eipsten-Barr Virus (EBV) is one of theetiological agents of Nasopharyngeal Carcinoma (NPC) and infected B lymphocyte that cause transformation of it to LymphoblastoidCell Line and expresses several antigens. One of them is known as Latent membrane Protein 2A (LMP2A). These antigens is the maintarget of Cytotoxic T lymphocyte (CTL) in immune system surveillance by recognizing an epitope Human Leukocyte Antigen (HLA)class I complexes which expressed on the target cell surface. Beside EBV, there are other factors that. Research of the HLA class I antigenis one of the immune genetic system that has the ability as genetic sensitivity to the disease. The research in NPC patients is not tobe done to show representative for of population in Indonesia especially in Java. The aim of the study was to know the associationbetween HLA class I profile and NPC patients in Java population and to isolate lymphocyte from peripheral blood 24 NPC patients formicrolymphocytotoxicity test with Terasaki Plate derived from UCLA-USA. The results is significantly associated to HLA – A 24 (RR 2.25),HLA A2 (RR 1.635) and HLA A11 (RR 1.065). Based on these HLA class 1 profile as an immune genetics marker on NPC is one of themost important target. In order to develop EBV vaccine in the future, this is necessary especially for Java Population in Indonesia.